2014
DOI: 10.1089/ars.2013.5600
|View full text |Cite
|
Sign up to set email alerts
|

Binding to WGR Domain by Salidroside Activates PARP1 and Protects Hematopoietic Stem Cells from Oxidative Stress

Abstract: Aims: A component of the base excision repair pathway, poly(ADP-ribose) polymerase-1 (PARP1) functions in multiple cellular processes, including DNA repair and programmed cell death. We previously showed that Salidroside, a phenylpropanoid glycoside isolated from medicinal plants, prevented the loss of hematopoietic stem cells (HSCs) in native mice and rescued HSCs repopulating in transplanted recipients under oxidative stress. The aim of this study was to investigate the mechanism by which PARP1 activation by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“…Li et al [110] observed that salidroside specifically failed to inhibit H 2 O 2 -induced DNA strand breaks in hematopoietic stem cells (HSCs) from mice with poly(ADP-ribose)polymerase-1 (PARP-1), a component of the base excision repair pathway, deletion, but not those with deficiency in homologous recombination, nonhomologous end-joining, nucleotide excision repair, or fanconi anemia pathway. In addition, they observed that salidroside enhanced the PARP-1 activity to prevent quiescent HSCs from oxidative stress-induced cycling and subsequent exhaustion in native animals and self-renewal defect in transplanted recipients [111]. Further study by the same group demonstrated the binding of salidroside to the tryptophan-glycine-arginine-rich domain of PARP-1[111].…”
Section: Mechanisms Of Rhodiola Rosea L and Its Active Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al [110] observed that salidroside specifically failed to inhibit H 2 O 2 -induced DNA strand breaks in hematopoietic stem cells (HSCs) from mice with poly(ADP-ribose)polymerase-1 (PARP-1), a component of the base excision repair pathway, deletion, but not those with deficiency in homologous recombination, nonhomologous end-joining, nucleotide excision repair, or fanconi anemia pathway. In addition, they observed that salidroside enhanced the PARP-1 activity to prevent quiescent HSCs from oxidative stress-induced cycling and subsequent exhaustion in native animals and self-renewal defect in transplanted recipients [111]. Further study by the same group demonstrated the binding of salidroside to the tryptophan-glycine-arginine-rich domain of PARP-1[111].…”
Section: Mechanisms Of Rhodiola Rosea L and Its Active Componentsmentioning
confidence: 99%
“…In addition, they observed that salidroside enhanced the PARP-1 activity to prevent quiescent HSCs from oxidative stress-induced cycling and subsequent exhaustion in native animals and self-renewal defect in transplanted recipients [111]. Further study by the same group demonstrated the binding of salidroside to the tryptophan-glycine-arginine-rich domain of PARP-1[111]. …”
Section: Mechanisms Of Rhodiola Rosea L and Its Active Componentsmentioning
confidence: 99%
“…A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 6 The collection of human umbilical cords was approved by the Ethics Committee of Tongji Medical…”
Section: Cell Culturementioning
confidence: 99%
“…Previous studies have shown that SAL activates DNA repair enzyme poly (ADP-ribose) polymerase (Parp-1) and protects cells from oxidative stress [5,6]. A recent study has reported that SAL can efficiently decrease atherosclerotic plaque formation in low-density lipoprotein receptor-deficient mice [7], but the mechanism of its anti-atherosclerotic action has not been shown.…”
Section: Introductionmentioning
confidence: 99%
“…Salidroside is the main bioactive compound in Rhodiola rosea extracts. Salidroside prevented the loss of hematopoietic stem cells in mice under oxidative stress via activating DNA repair enzyme poly (ADP-ribose) polymerase-1 (PARP-1) activity [181]. Salidroside also inhibited cancer cell migration and invasion, as well as xenograft tumor growth of human glioma cells in nude mice [182, 183].…”
Section: Approaches or Agents With Both Anti-aging And Anti-cancermentioning
confidence: 99%